Kinetics and Mechanism of Acid Bromate Oxidation of2-Hydroxy-1-naphthalideneanil - N. Pol, Umesh; S. Yamgar, Ramesh; Dodwad, S.S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of the Schiff base, 2-hydroxy-1-naphthalideneanil by potassium bromate in aquo-acetic acid medium has been studied. The reaction is found to obey the first order rate equation. The study is carried out at five different temperatures. The study is also undertaken by change in the concentration of oxidant, change in the concentration of HClO4 and change in ionic strength. These changes also show first order behaviour. The thermodynamic parameters ΔE, ΔH*, ΔG* and ΔS* have been calculated and reported. The frequency factor (A) is also computed. Ionic strength effects show a negative effect on rate constant.